Penilaian Mutu Secara Organoleptik Ikan Patin (Pangasius sp.) Segar Di Pasar Bauntung, Banjarbaru, Kalimantan Selatan - Fadel Muhammad Sudarmanto; Imam Setiawan (LPPM Universitas Terbuka, 2022)
The level of fish consumption in South Kalimantan, especially by the people of Banjarbaru is very high. In some traditional markets, the process of handling catfish (Pangasius sp.) still needs to be reviewed for their quality management, so the quality of catfish received by consumers is still in a good condition. The purpose of this study was to assess the organoleptic quality of fresh catfish during sales at Bauntung market in Banjarbaru city. In this study, the method used was organoleptic testing with the score test method. The score test used was determining quality levels based on a scale of 1 to 9, with 1 as the lowest value and 9 as the highest value by using the organoleptic score sheet of fresh fish performed by 7 untrained panelists. Observation method used using score sheets to observe fish handling activities by 2 different sellers. Observations were made at 10:00 and 15:00, local time. On the observation at 10:00, the two groups of catfish retained their good organoleptic qualities, on the other hand, at 15:00, there was a decrease in organoleptic quality in both catfish groups. For both groups and at both observation times, the organoleptic quality scoring was higher than 7. The score showed that the catfishes at Bauntung Market maintained their fresh qualities and were suitable for consumption after handling.